Research on Liangshan Yi Embroidery Innovative Product Consumer Demand and Design Optimization - Wang, Lixia; Mayusoh, Chanoknart; Inkuer, Akapong; Suwannatat, Permsak (Journal of Cultural Analysis and Social Change, 2025)
On the premise of maintaining the authenticity of the local culture of Liangshan Yi embroidery, this study summarized the influencing factors of innovative design through expert interviews and group discussions, designed questionnaires for several dimensions that affect consumers' purchase intentions, and conducted consumer questionnaire surveys to understand consumers' preferences for each design element, grasp the real needs of market consumers for Liangshan Yi embroidery innovative products, and put forward targeted optimization suggestions to guide subsequent product design.